9 Powerful Practices of Really Great Teams - Kohn, Stephen; O'Connell, Vincent (Ascent Audio, 2018)
Increasingly, organizations count on project teams to develop products and deliver services to their customers. Consequently, effective teamwork and team leadership are integral components of an organization's success. In 9 Powerful Practices of Really Great Teams, Stephen E. Kohn and Vincent D. O'Connell define the essence of superior performance by project teams at work, and identify nine attributes of team membership and team leadership that set the stage for accomplishment of group objectives. Kohn and O'Connell bring these proven strategies to life with real-world examples drawn from decades of experience.